MPPT Based on Sinusoidal Extremum-Seeking Control in PV Generation. (7th March 2012) - Leyva, R.; Olalla, C.; Zazo, H.; Cabal, C.; Cid-Pastor, A.; Queinnec, I.; Alonso, C.
Abstract : The paper analyses extremum-seeking control technique for maximum power point tracking circuits in PV systems. Specifically, the paper describes and analyses the sinusoidal extremum-seeking control considering stability issues by means a Lyapunov function. Based on this technique, a new architecture of MPPT for PV generation is proposed. In order to assess the proposed solution, the paper provides some experimental measurements in a 100 W prototype which corroborate the effectiveness of the approach.